2013
DOI: 10.1002/bit.24858
|View full text |Cite
|
Sign up to set email alerts
|

Peak antibody production is associated with increased oxidative metabolism in an industrially relevant fed‐batch CHO cell culture

Abstract: Cell metabolism can vary considerably over the course of a typical fed-batch antibody production process. However, the intracellular pathway alterations associated with various phases of growth and antibody production have yet to be fully elucidated using industrially relevant production hosts. Therefore, we performed (13)C labeling experiments and metabolic flux analysis (MFA) to characterize CHO cell metabolism during four separate phases of a fed-batch culture designed to closely represent industrial proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
266
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(302 citation statements)
references
References 50 publications
33
266
3
Order By: Relevance
“…In addition, lactate is also consumed (Q Lac ) [14,55], which in this case was modelled and triggered by the depletion of glutamate. Antibody production (q i , Equation 17) is specific for each cell cycle phase.…”
Section: Cyclins Growth Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lactate is also consumed (Q Lac ) [14,55], which in this case was modelled and triggered by the depletion of glutamate. Antibody production (q i , Equation 17) is specific for each cell cycle phase.…”
Section: Cyclins Growth Functionsmentioning
confidence: 99%
“…Recently, metabolic flux analysis (MFA) has become a key tool for the study of mammalian cell cultures aiming at improving productivity and product quality. These studies [11][12][13][14] provide valuable insight on cell behaviour and assist in understanding cell metabolism. However, they neglect the intrinsic heterogeneity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To meet this demand, a variety of strategies have been employed to develop efficient biopharmaceutical manufacturing processes. These strategies include: 1) maximizing the productivity of the manufacturing cell line by the judicious use of expression systems for optimal transcription and translation of the therapeutic protein [2]; 2) engineering the transfection host cell line for efficient post-translational modification and secretion [3]; and 3) improving the cell culture process including media optimization [4][5][6][7][8], developing advanced feeding strategies [9,10] which in turn increases the culture density. Additionally, robust and highly productive host cell lines can be deployed by increasing the efficiency of gene expression that regulates proliferation [11] survival and longevity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Martínez et al 61 showed that a CHO cell line grown in a batch culture had a six times higher energy efficiency when consuming lactate as compared to the situation where lactate was produced. Using isotopic labeling in combination with metabolic flux analysis, Sengupta et al 72 and Templeton et al 73 both reported higher metabolic fluxes through the pentose phosphate pathway (PPP) and TCA cycle during the stationary phase as compared to the growth phase of CHO cell cultures. Furthermore, Templeton et al 73 showed that the high PPP and TCA activities are associated with peak mAb production.…”
Section: Introductionmentioning
confidence: 99%
“…Using isotopic labeling in combination with metabolic flux analysis, Sengupta et al 72 and Templeton et al 73 both reported higher metabolic fluxes through the pentose phosphate pathway (PPP) and TCA cycle during the stationary phase as compared to the growth phase of CHO cell cultures. Furthermore, Templeton et al 73 showed that the high PPP and TCA activities are associated with peak mAb production. Results from Wahrheit et al 74 suggested that the metabolic shift in different culture phases of CHO cells is controlled by glycolytic regulation which affects the intracellular pyruvate availability.…”
Section: Introductionmentioning
confidence: 99%